Real-world experience with the use of diazoxide among people living with congenital hyperinsulinism and their caregivers - Pasquini, Tai L. S.; Rohli, Kristen E.; Almeida, Fiona J.; Banerjee, Indraneel; Dastamani, Antonia; De Leon, Diva D.; Lopez, Lauren N.; Thornton, Paul S.; Raskin, Julie (Frontiers in Endocrinology, 2025)
IntroductionCongenital hyperinsulinism (HI) is a rare disease that causes severe hypoglycemia. Diazoxide is the first-line treatment; however, many individuals using diazoxide continue to experience hypoglycemia. Diazoxide is associated with side effects that impact life and well-being.MethodsThe study utilized a mixed-methods approach combining structured, survey-based cross-sectional quantitative data from the HI Global Registry (HIGR) (n=165, 89% were caregivers), of whom 75% reported current diazoxide use, with qualitative interviews with caregivers (n=12) and individuals with HI (n=6). This is the first mixed-methods study to focus on the experience of diazoxide treatment as reported by the individual taking the medicine and/or their caregiver.ResultsOf HIGR participants, 93% reported at least one side effect, including hypertrichosis (89%), loss of appetite (40%), facial changes (23%), and swelling (22%) with diazoxide use. In HIGR, 37% of people currently on diazoxide reported experiencing hypoglycemia up to several times per week. Interview participants described how these side effects, the drug’s taste, and feeding difficulties associated with HI and diazoxide adversely impacted daily life.DiscussionDiazoxide is commonly used by families living with HI, but a significant proportion reported hypoglycemia. Individuals who experienced better glycemic control with the drug were less critical of side effects. Combining HIGR data with in-depth interviews facilitated understanding of day-to-day life, which can help implement measures to better support families managing HI. This study prompts the need for improved treatment options and for clinicians to utilize the International HI Care Guideline to optimize diazoxide therapy.